Composição, estrutura e diversidade em floresta ombrófila na Reserva Biológica do Jaru-RO - Azevedo, Guilherme Benelli de (2014)
Located in the northeast of the State of Rondônia, Jaru Biological Reserve is located in one of the areas of great diversity and endemism of the Amazonian Biome. Due to the purpose of this conservation unit and the scarcity of publications on the flora of this region in the Central Amazon, this work aims to contribute to the knowledge of the phytosociological structure and tree species diversity in this area. The data were obtained by sampling of 3 transects with dimensions of 10 x 500 m, subdivided into plots of 10 x 50 m and established in a systematic way, where all individuals were registered with diameter breast height (dbh) ≥ 10 cm. The species have been recognized by the common name preliminarily and taxonomic identification, after they had their Phytosociological Parameters calculated. 862 individuals were recorded, distributed in 49 botanical families, 144 genera and 298 species. Most families well represented with 55 species were Fabaceae, Sapotaceae with 23, Moraceae with 19, Annonaceae with 15, Malvaceae 14, Burseraceae. with 13, Lauraceae with 13, with 12, Meliaceae Chrysobalanaceae with 10 and Myristicaceae with 9 species. The density was 574.67 individuals/ha and basal area was 34.78 m2/ha, the species with the highest importance value (%) in descending order were: Attalea speciosa Mart. (4.75), Peltogyne excelsa Ducke (4.05), Bertholletia excelsa Bonpl. (3.02), Ficus capensis Thunb. (2.76), Euterpe precatoria Mart. (2.69), Theobroma microcarpum Mart. (2.37), Dipteryx odorata (Aubl.) Willd. (2.15), Cariniana decandra Ducke (1.74), Dialium guianense (Aubl.) Sandwith (1.68), Eschweilera coriacea (DC.) S.A. Mori (1.61). The diversity Shannon index was 5.10 nats/ind and the similarity of Sorensen of 45.7% maximum. The diversity using Shannon found was 5.10 nats/ind and Sorensen Similarity maximum of 45.7%. On these results, it was possible to conclude that the transects showed distinct characteristics, the study showed characteristics corresponds to palm ombrophilous rain forest, being found a high diversity.